A novel method using body surface steel ball as a reference scale to measure the left atrial appendage for optimal selection of Watchman device - Jin, He; Feng, Mingjun; Du, Xianfeng; Wang, Binhao; Yu, Yibo; Fu, Guohua; Shen, Caijie; Chu, Huimin (Frontiers in Cardiovascular Medicine, 2025)
BackgroundLeft atrial appendage closure (LAAC) is an alternative to oral anticoagulation for stroke prevention in non-valvular atrial fibrillation (AF). Selecting the appropriate size of Watchman device is very important intra-procedure. There are several methods have been reported to measure the left atrial appendage (LAA), but each of them has its limitations.ObjectiveWe investigated the efficacy and safety of using the novel “steel ball method” compared to using the traditional “sheath method” and TEE during procedure of LAAC with Watchman device in AF patients.MethodsPatients with atrial fibrillation who underwent LAAC with Watchman device at The First Affiliated Hospital of Ningbo University from January 2018 to December 2021 were retrospectively analyzed. A 10 mm-diameter steel ball was placed on patient's body surface at the pulmonary valve auscultation zone before procedure. The maximum LAA ostium diameter, maximum LAA depth, and 1st sheath marker band length were measured under x-ray fluoroscopy, using the delivery sheath, pigtail sheath, and steel ball as references, respectively, which we called the delivery sheath group, pigtail sheath group and steel ball group. The maximum LAA ostium diameter and maximum LAA depth were also measured by TEE. All Watchman devices were selected based on the measurement of LAA by “steel ball method”. The position of Watchman device and presence of peri-device leakage (PDL) were assessed using transesophageal echocardiography (TEE) before and after the release.ResultsEventually a total of 169 patients [63.3% male, age 69 (44–87) years, 73.4% persistent or permanent AF, CHA2DS2-VASc score 4.31 ± 1.54, HAS-BLED score 2.74 ± 1.15, left atrial diameter 44.09 ± 7.55 mm] underwent Watchman device implantation successfully were enrolled. The mean maximum LAA ostium diameter measured in steel ball group (24.73 ± 3.39 mm) was significantly higher than that in delivery sheath group (20.04 ± 3.24 mm, p < 0.001) and pigtail sheath group (22.48 ± 3.74 mm, p < 0.001), while was not significantly different from the results measured by TEE (24.39 ± 4.13 mm, p = 0.176). The difference between 1st sheath marker band length measured in steel ball group and the true length (21 mm) was 0.29 ± 0.61 mm, which was significantly less than that in delivery sheath group (4.22 ± 1.42 mm) and pigtail sheath group (2.17 ± 1.90 mm) (both p < 0.001). Finally, the success rate of Watchman device implantation is 98.8%, with no serious intra-procedure complication. 2 patients (1.2%) occurred pericardial tamponade after procedure. 98.8% and 97.0% of patients had either no or slight (≤3 mm) PDL with immediate and 45 days post-procedural TEE scans, respectively. Device-related thrombosis (DRT) was detected in 1 patient (0.6%) and 2 patients (1.2%) had ischemic stroke during follow-up.ConclusionsIn LAAC, the novel method using body surface steel ball as a reference scale to measure the left atrial appendage and guide the selection of Watchman device is accurate, effective, and safe. The size of Watchman device may be too small if selection is based on the measurement results with “sheath method”, which can lead to unsatisfactory outcome of the procedure.